2006
DOI: 10.1016/j.ydbio.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sox2 in the development of the mouse neocortex

Abstract: The mammalian neocortex is established from neural stem and progenitor cells that utilize specific transcriptional and environmental factors to create functional neurons and astrocytes. Here, we examined the mechanism of Sox2 action during neocortical neurogenesis and gliogenesis. We established a robust Sox2 expression in neural stem and progenitor cells within the ventricular zone, which persisted until the cells exited the cell cycle. Overexpression of constitutively active Sox2 in neural progenitors result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
213
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(241 citation statements)
references
References 89 publications
20
213
0
3
Order By: Relevance
“…Here we demonstrate that this probably occurs through induction of Sox2. This is in contrast to the eye and neocortex, where it has been shown that Sox2 appears to act upstream of Notch signaling (9,18). However, the demonstration that inhibition of Notch signaling within an existing prosensory domain leads to down-regulation of Sox2 expression suggests that the role of Notch in Sox2 expression extends beyond the period of Sox2 induction.…”
Section: Discussionmentioning
confidence: 87%
“…Here we demonstrate that this probably occurs through induction of Sox2. This is in contrast to the eye and neocortex, where it has been shown that Sox2 appears to act upstream of Notch signaling (9,18). However, the demonstration that inhibition of Notch signaling within an existing prosensory domain leads to down-regulation of Sox2 expression suggests that the role of Notch in Sox2 expression extends beyond the period of Sox2 induction.…”
Section: Discussionmentioning
confidence: 87%
“…For example, progenitors in the VZ at early stages of corticogenesis express a number of transcription factors (such as Fezf2, Otx1, Sox2, and Emx2) that are maintained by their progeny as young neurons populate the deep layers [11][12][13][14]. However, at middle stages of neurogenesis, as progenitors begin to produce the neurons of layers 4 through 2, the cells undergo a series of interesting cellular and molecular alterations.…”
Section: Cellular Studies Of Cell Fate Determination Suggest a Progrementioning
confidence: 99%
“…Coupling of angiogenesis and neurogenesis after stroke H Teng et al in the levels of Sox2 mRNA, a gene involved in the maintenance of neural progenitor cell identity (Bani-Yaghoub et al, 2006;Graham et al, 2003), and an increase in the levels of Hes6 mRNA, a gene that promotes neuronal differentiation but inhibits astrocyte differentiation (Gratton et al, 2003;Jhas et al, 2006) (Figure 3). However, when normal SVZ cells were cocultured with stroke RBECs in the growth or differentiation medium in the presence of SU1498, a VEGFR2 antagonist, the number of BrdU + (Figures 2C to E) and Tuj1 + ( Figures 2I, 2J, and 2O) cells was significantly reduced, while the number of GFAP + cells did not significantly change (26.8% ± 1.8% versus 23.5% ± 4.0% in the SU1498 group, Figures 2M, 2N, and 2P).…”
Section: Endothelial Cells Activated By Stroke Increase Proliferationmentioning
confidence: 99%